Adverse childhood experiences among people with schizophrenia at comprehensive specialized hospitals in Bahir Dar, Ethiopia: a comparative study - Assefa Fentahun, Birhanu; Belete Mossie, Tilahun; Damtew Hailu, Rekik; Bete, Tilahun; Moges Demeke, Solomon (Frontiers in Psychiatry, 2024)
BACKGROUND: People who have encountered adverse childhood experiences (ACEs) are predisposed to developing schizophrenia, experiencing exacerbated symptoms, and facing an elevated risk of disease relapse. It is imperative to evaluate the prevalence of ACEs to comprehend the specific attributes of this condition and enable the implementation of suitable interventions. The aim of this study was to assess the prevalence of ACEs and its determinants among people with schizophrenia and the patient attendants in Bahir Dar, Ethiopia. A comparative cross-sectional study was carried out at the Comprehensive Specialized Hospitals in Bahir Dar, Ethiopia, from April 26 to June 10, 2023. A total of 291 individuals with schizophrenia and 293 individuals from the patient attendants were selected using a systematic random sampling method. A proportional odds model ordinal logistic regression analysis was used to identify the factors associated with ACEs. The occurrence of at least one ACE among individuals diagnosed with schizophrenia was 69.4%, while patient attendants had a 46.8%, as indicated by the Chi-square test, which showed a significant difference at p <0.05. The study findings indicated that individuals with schizophrenia who have encountered four or more ACEs are more inclined to have lower educational attainment ), low resilient coping mechanisms (AOR: 2.07 [1.11 -3.90]), and poor social support ). Conversely, factors such as rural residency, illiteracy, and heightened attachment-related anxiety were found to be notably associated with the patient attendants. In this study, the substantial prevalence of ACEs emphasized the necessity for ACE screening and the implementation of evidence-based interventions to address and alleviate the overall burden of ACEs.